2-tier in-plane motion correction and out-of-plane motion filtering for contrast-enhanced ultrasound - Ta, Casey N. (2014)
OBJECTIVES: Contrast-enhanced ultrasound (CEUS) cines of focal liver lesions (FLL) can be quantitatively analyzed to measure tumor perfusion on a pixel-by-pixel basis for diagnostic indication. However, CEUS cines acquired freehand and during free breathing cause non-uniform in-plane and out-of-plane motion from frame to frame. These motions create fluctuations in the time-intensity curves (TIC), reducing accuracy of quantitative measurements. Out-of-plane motion cannot be corrected by image registration in 2D CEUS and degrades the quality of in-plane motion correction (IPMC). A 2-tier IPMC strategy and adaptive out-of-plane motion filter (OPMF) are proposed to provide a stable correction of non-uniform motion to reduce the impact of motion on quantitative analyses. MATERIALS AND METHODS: 22 cines of FLLs were imaged with dual B-mode and contrast specific imaging to acquire a 3-minute TIC. B-mode images were analyzed for motion, and the motion correction was applied to both B-mode and contrast images. For IPMC, the main reference frame was automatically selected for each cine, and subreference frames were selected in each respiratory cycle and sequentially registered toward the main reference frame. All other frames were sequentially registered toward the local subreference frame. Four OPMFs were developed and tested: subsample Normalized Correlation (NC), subsample Sum of Absolute Differences (SAD), mean frame NC, and histogram. The frames that were most dissimilar to the OPMF reference frame using one of the four above criteria in each respiratory cycle were adaptively removed by thresholding against the low-pass filter of the similarity curve. OPMF was quantitatively evaluated by an out-of-plane motion metric (OPMM) that measured normalized variance in the high-pass filtered time-intensity curve within the tumor region-of-interest with low OPMM being the goal. IPMC and OPMF results were qualitatively evaluated by two blinded observers who ranked the motion in the cines before and after various combinations of motion correction steps. RESULTS: Quantitative measurements showed that 2-tier IPMC and OPMF improved imaging stability. With IPMC, the NC B-mode metric increased from 0.504 ± 0.149 to 0.585 ± 0.145 over all cines (p < 0.001). 2-tier IPMC also produced better fits on the contrast-specific TIC than industry standard IPMC techniques: (p < 0.02). IPMC and OPMF were shown to improve goodness-of-fit for pixel-by-pixel analysis (p < 0.001). OPMF reduced variance in the contrast-specific signal as shown by a median decrease in the OPMM of 49.8%. 2-tier IPMC and OMPF were also shown to qualitatively reduce motion. Observers consistently ranked cines with IPMC higher than the same cine before IPMC (p < 0.001) as well as ranked cines with OPMF higher than when they were uncorrected. CONCLUSION: The 2-tier sequential IPMC and adaptive OPMF significantly reduced motion in 3-minute CEUS cines of FLLs thereby overcoming the challenges of drift and irregular breathing motion in long cines. The 2-tier IPMC strategy provided stable motion correction tolerant of out-of-plane motion throughout the cine by sequentially registering subreference frames that bypassed the motion cycles, thereby overcoming the lack of a nearly stationary reference point in long cines. OPMF reduced apparent motion by adaptively removing frames imaged off-plane from the automatically selected OPMF reference frame, thereby tolerating non-uniform breathing motion. Selection of the best OMPF by minimizing OPMM effectively reduced motion under a wide variety of motion patterns applicable to clinical CEUS. These semi-automated processes only required user input for region-of-interest selection and can improve the accuracy of quantitative perfusion measurements.